Synthesis and Characterization of Mn(II) and Zn(II) Complexes with Cimetidine - Srivastava, Savita; Shrivastava, N.M.; Iqbal, S.A. (Asian Journal of Chemistry, 2010)
Inflammation is an essential component of all ulcers. Complexes of metals found to enhance antiulcer activity of drug. Cimetidine is the most useful drug in the management of peptic and duodenal ulcers. The complexes of cimetidine may be of higher biological interest. In the present work, the synthesis and characterisation of Mn(II) and Zn(II) with cimetidine is reported.